Transparent poly(ether sulfone) nanocomposite film with low thermal expansion coefficient for flexible display substrates. (1st November 2021) - Vo, Nhat Tri; Yoo, Pil Jin; Yi, Gi-ra; Schroeder, Marc; Kim, Dukjoon
Abstract: Optically transparent poly(ether sulfone) (PES) nanocomposite films with low coefficients of thermal expansion (CTE) were synthesized for use as flexible display substrates. Boehmite (AlOOH) nanowires ~10 nm in diameter were synthesized and applied as fillers to reduce the CTE of the PES film. PES molecules were slightly sulfonated to enhance their compatibility with AlOOH nanowires via hydrogen bonding. The aspect ratio of the AlOOH nanowires had a significant effect on the CTE of nanocomposite films. At a fixed filler concentration of 15 wt%, the AlOOH nanowires with an aspect ratio of 100 reduced the CTE of the PES film by 73.6 % from 65.5 ppm/°C to 17.3 ppm/°C, while those with an aspect ratio of 20 reduced it only by 28 %. Although such a huge reduction of CTE was provided by AlOOH nanowires, the optical transmittance was still 96 % of the pristine PES film because the refractive indices of PES and AlOOH nanowires were the same. Introduction of AlOOH nanowires also enhanced the thermal and dimensional stabilities of the PES film.